2020
DOI: 10.1155/2020/9701285
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Nonalcoholic Hepatic Steatosis by Shenling Baizhu Powder: Involvement of Adiponectin-Induced Inhibition of Hepatic SREBP-1c

Abstract: Background. Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease worldwide, and its incidence is increasing annually, but there is currently no specific drug for treating NAFLD. Shenling Baizhu powder (SL) is a safe herbal compound commonly used in clinical practice. Our previous research has shown that SL has the effect of preventing NAFLD, but its specific mechanism has not been determined. In this study, the potential mechanism of SL on NAFLD was explored by in vivo experiments. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In treating type 2 diabetes, Chinese herbal formulas, as one of the important constituents in traditional Chinese medicine (TCM), are now used as a potential adjuvant therapy for treating various diseases by modulating gut microbiota and promoting host metabolism ( 54 57 ). Drugs with oral administration can promote the host metabolism and modulate the structure of gut microbiota ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…In treating type 2 diabetes, Chinese herbal formulas, as one of the important constituents in traditional Chinese medicine (TCM), are now used as a potential adjuvant therapy for treating various diseases by modulating gut microbiota and promoting host metabolism ( 54 57 ). Drugs with oral administration can promote the host metabolism and modulate the structure of gut microbiota ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The syndromes in patients with NAFLD can be classified into the following types 41 : (i) spleen-deficiency and phlegm-turbid stagnation; (ii) stagnation of liver-qi; (iii) accumulated damp-heat; (iv) stasis blocking channels and (v) deficiency of liver and kidney. According to these TCM syndromes, the treatment principle and the relevant classical formulas to treat NAFLD are as follows: (i) formulas for invigorating spleen, removing dampness and phlegm: shenlingbaizhu powder (Tai Ping Hui Min He Ji Ju Fang) 42 , 43 , simiao powder (Cheng Fang Bian Du) 44 , sanziyangqin decoction (Han Shi Yi Tong) 45 ; (ii) formulas for relieving liver and regulating qi: xiaochaihu decoction ( Shang Han Lun ) 46 , chaihushugan powder ( Jingyue Complete Library ) 47 , 48 , 49 ; (iii) formulas for clearing heat, promoting dampness and dispersing knot: dachaihu decoction ( Treatise on Febrile Disease ) 50 , 51 , yinchenhao decoction ( Shang Han Lun ) 52 ; (iv) formulas for promoting blood circulation and dissipating blood stasis: taohongsiwu decoction ( The Golden Mirror of Medicine ) 53 ; (v) formulas for warming yng and invigorating spleen: chaihulizhong decoction (Shang Han Lun) 54 , lingguizhugan decoction ( Jin Gui Yao Lue ) 55 , 56 , 57 , fuzilizhong decoction (San Yin Ji – Bing Zheng Fang Lun) 58 , sini powder (Shang Han Lun) 59 , 60 , 61 , ganjianglingzhu decoction ( Jin Gui Yao Lue ) 62 . The regulatory effects and relevant mechanisms of the classical formulas of TCM treating NAFLD are shown in Table 1 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Therapeutic Effects and Mechanisms Of Tcm In Treating Nafldmentioning
confidence: 99%
“… Treatment principle Chinese medicinal formula Model Effects of TCM treating NAFLD Ref. Invigorate spleen, remove dampness and phlegm Shenlingbaizhu powder (SLBZS) HFD-induced NAFLD rats CDAA-fed rats ↓ Hepatic injury ↓ Lipid accumulation ↓ The serum level of endotoxin, TNF- α , IL-1 β ↓ TLR4, TRAF6 in the liver tissue ↑ The abundance of intestinal microbiota ↑ The abundance of short-chain fatty acid ↑ Adiponection ↓ SREBP-1c, FAS 42 , 43 Simiao powder (SMS) HFHS-induced NAFLD mice ↓ Acly , Fas , Acc , Scd1 ↓ IL-1 β , NLRP-3 ↓ The biosynthesis of fatty acids ↑ Insulin secretion pathway ↑ Gut microbiota composition 44 Sanziyangqin decoction (SZYQT) HFD-induced NAFLD mice ↓ Hepatosteatosis ↓ TNF- α ↓ Inflammatory cell infiltration in liver tissues ↑ Insulin resistance ↑ p-AKT; ↓ apoptosis 45 Relieve liver and regulate Qi Xiaochaihu decoction (XCHT) Patients with NAFLD ↑ Lipid metabolism 46 Chaihushugan powder (CHSGS) HFD-induced NAFLD/NASH rats High fat and sugar emulsion-induced NAFLD rats ↓ Enterobacteriaceae, Staphylococcaceae families and Veillonella genus ↑ Anaeroplasma genus ↓ Fat accumulation ↓ Inflammatory factors (TNF- α , IL-1 β , IL-18, IL-6) ↓ NLRP3, ASC, CASPASE-1 ↓ TLR4, p-p38 MAPK ↑ Adiponectin; ↓ leptin 47 , 48 , 49 Clear heat, promote dampness and disperse knot Dachaihu decoction (DCHT) Patients with NAFLD High-fat high-fructosediet-induced NAFLD rats ↓ TNF- α , TGF- β , NF- κ B, TLR4 50 , 51 Yinchenhao decoction (YCHT) …”
Section: Therapeutic Effects and Mechanisms Of Tcm In Treating Nafldmentioning
confidence: 99%
“…Evidence from animal and cell studies indicated that SLBZP prevents NAFLD/NASH progression through various mechanisms. The resulting diverse pharmacological effects are as follows: (1) decreased serum level of total cholesterol (TC) and endotoxin, TNF-α, IL-β, protein expression related to the toll-like receptor 4 (TLR4) pathway, alleviated hepatic steatosis via an increased abundance of beneficial gut microbiota, and decreased levels of lipopolysaccharide (LPS) in the portal vein; 43 (2) activated sirtuin1 (SIRT1) and regulation of glycerophospholipid and glycerolipid metabolism; 44 (3) increased levels of adiponectin in the liver and serum and inhibited expression of sterol regulatory element-binding protein 1c (SREBP-1c); 45 (4) reversal of differential expression of 28 miRNAs related to metabolism by modulating hepatic miRNA expression and the target pathways; 46 (5) a suppressed p38 mitogen-activated protein kinase (p38 MAPK) pathway in liver Kupffer cells (KCs) for an anti-inflammatory effect. 47 Chaihu Shugan San Powder.…”
Section: Traditional Natural Product Formulas and Historymentioning
confidence: 99%